Liquidity and the Law of One Price: The Case of the Futures‐Cash Basis - ROLL, RICHARD; SCHWARTZ, EDUARDO; SUBRAHMANYAM, AVANIDHAR (Journal of Finance, 2007)
ABSTRACT Deviations from no‐arbitrage relations should be related to market liquidity, because liquidity facilitates arbitrage. At the same time, a wide futures‐cash basis may trigger arbitrage trades and, in turn, affect liquidity. We test these ideas by studying the dynamic relation between stock market liquidity and the index futures basis. There is evidence of two‐way Granger causality between the short‐term absolute basis and liquidity, and liquidity Granger‐causes longer‐term absolute bases. Shocks to the absolute basis predict future stock market liquidity. The evidence suggests that liquidity enhances the efficiency of the futures‐cash pricing system.